Technique to Investigate Pulverizing and Abrasive Performance of Coals in Mineral Processing Systems - Wojciech Grzegorzek (MDPI AG, 2021)
The operating costs of breaking coal particles into fine powder, to achieve optimum combustion for the boilers in a power plant, are made up of power input to carry on an energy intensive comminution mechanism and to overcome friction losses within pulverising machines. The operating costs also include the cost of the replacement of the processing system’s components due to wear. This study presents the development and application of an attrition test machine that enables an investigation of the factors that influence pulverizing efficiency. The attrition tester simulates grinding conditions in real vertical spindle mills. In this kind of mill, as with the tester, the size reduction process results from a shearing action during the redistribution of the coal particles. The redistribution and attrition within the coal bed are forced by movement of the rollers (or by a disc rotation, in the case of the tester). The testing method was oriented toward mechanical properties, i.e., internal friction shear strength, abrasiveness and grindability. This method enables facilitated testing procedures and a more exact simulation of grinding in vertical spindle coal mills. Ball-race mills and Loesche roller mills were used.